UNDERSTANDING THE WAGE PAYMENT SYSTEM IN THE PRIVATE SECTOR IN CAMBODIA:A LITERATURE REVIEW - Mardy Serey (Universitas Diponegoro, 2025)
This article provides a comprehensive literature review of the wage payment system in Cambodia’s private sector, examining its legal framework, implementation practices, challenges, and recent reforms. Drawing on academic studies, government reports, and publications from international organizations, the review highlights the evolution of Cambodia’s wage payment system through domestic policy reforms, the introduction of sector-specific minimum wages, and the country’s increasing integration into global supply chains. Key issues discussed include the limitations of the minimum wage policy, enforcement challenges, gender disparities, the role of labor inspections and collective bargaining, and the impact of digitalization on wage payments. Comparative perspectives from neighboring countries such as Vietnam and Thailand are presented to identify best practices and potential strategies for Cambodia. Despite progress, significant research gaps remain, particularly regarding wage practices in the informal sector and small and medium-sized enterprises (SMEs), as well as the long-term effects of wage reforms. The article concludes with recommendations for strengthening enforcement, expanding social protection, embracing digital innovations, and fostering international cooperation to advance fair and equitable wage practices in Cambodia.